The Influence of Cyberloafing and Employee Empowerment on Job Satisfaction (A Study on PT Inti Indosawit Subur) - Edbert, Jeffry; Adlina, Hafiza (Jurnal Ilmiah Wahana Pendidikan, 2025)
Integrating technology in digital era into daily life, poses challenges for companies in regulating employee activities during working hours. This study examines the impact of cyberloafing and employee empowerment on job satisfaction among PT Inti Indosawit Subur employees. Conducting a quantitative, associative research approach, data were collected from 76 employees through simple random sampling. Primary data were gathered via direct questionnaire distribution, and secondary data were sourced from literature reviews. Data analysis included instrument testing, classic assumption testing, multiple linear regression analysis, and hypothesis testing. Results indicate that cyberloafing (X1) has a positive but insignificant effect on job satisfaction (t-value = 0.195 < 1.993, sig = 0.846 > 0.05, regression coefficient = 0.025). Conversely, employee empowerment (X2) significantly enhances job satisfaction (t-value = 5.630 > 1.993, sig = 0.000 < 0.05, regression coefficient = 0.676). Combined, cyberloafing and employee empowerment explain 33.7% of job satisfaction, with the remaining 66.3% influenced by external factors not covered in this study.